Assessment of visual acuity in Elementary School students (Research, Society and Development, 2023)
• Objective: To evaluate the visual acuity of elementary school students. Method: Cross-sectional, descriptive and exploratory study, with a quantitative approach carried out with 95 students regularly enrolled from the 1st to the 5th year of a private school, in the western region of the state of Paraná. Data collection took place in the second academic semester of the year 2023 and, for this purpose; a questionnaire was used to collect sociodemographic data, prepared by the authors based on the literature and the Snellen table. According to its technical parameters, visual acuity was considered normal when greater than 20/30 or 0.7. Results: Of the students evaluated, 16.84% had low visual acuity and 83.16% did not show corresponding changes in acuity. Given the diagnosis of low acuity, referrals were made to an ophthalmologist. Conclusion: This study highlights the importance of early visual assessment in children, given its relevance for improving students' academic performance and quality of life. The use of tests and questionnaires is essential, but challenges such as raising parental awareness to undergo periodic evaluations by a specialist doctor persist. It is crucial to incorporate visual acuity assessment as a regular practice in schools, promoting eye health, identifying visual problems and qualifying students' academic performance.